Downregulation of TAP38/PPH1 enables LHCII hyperphosphorylation in Arabidopsis mutant lacking LHCII docking site in PSI - Rantala, Marjaana (FEBS Lett, 2016)
Redox‐regulated reversible phosphorylation of the light‐harvesting complex II (LHCII) controls the excitation energy distribution between photosystem (PS) II and PSI. The PsaL and PsaH subunits of PSI enable the association of pLHCII to PSI. Here, we show that the failure of the psal mutant to dock pLHCII to PSI induces excessive phosphorylation of LHCII, primarily due to a marked downregulation of the TAP38/PPH1 phosphatase occurring at post‐transcriptional level. TAP38/PPH1 is shown to be associated with megacomplex that contains both photosystems in a light‐ and LHCII‐PSII core‐phosphorylation‐dependent manner. It is suggested that proper megacomplex‐related association of TAP38/PPH1 protects it against degradation.